2014
DOI: 10.1038/ncomms4313
|View full text |Cite
|
Sign up to set email alerts
|

Novel polymer-free iridescent lamellar hydrogel for two-dimensional confined growth of ultrathin gold membranes

Abstract: Hydrogels are generally thought to be formed by nano-to micrometre-scale fibres or polymer chains, either physically branched or entangled with each other to trap water. Although there are also anisotropic hydrogels with apparently ordered structures, they are essentially polymer fibre/discrete polymer chains-based network without exception. Here we present a type of polymer-free anisotropic lamellar hydrogels composed of 100-nm-thick water layers sandwiched by two bilayer membranes of a self-assembled nonioni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
96
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(99 citation statements)
references
References 36 publications
1
96
0
Order By: Relevance
“…35,36 The ordered structure gives the solution an iridescent color due to its Bragg reflectance of visible light. The synthesis of ultrathin polyacrylamide nanosheets was accomplished in a supramolecular system with an HGM concentration of 2 wt % in this study.…”
Section: Resultsmentioning
confidence: 99%
“…35,36 The ordered structure gives the solution an iridescent color due to its Bragg reflectance of visible light. The synthesis of ultrathin polyacrylamide nanosheets was accomplished in a supramolecular system with an HGM concentration of 2 wt % in this study.…”
Section: Resultsmentioning
confidence: 99%
“…In the presence of 2D templates, such as lamellar hydrogels, 33,41 graphene oxide, 28 graphite 55,9597 and lyotropic liquid crystals, 98,99 metal nanocrystals can be directed or confined to grow into nanoplates and nanosheets under appropriate conditions. For example, an iridescent hexadecylglyceryl maleate (HGM) hydrogel has been used to synthesize single-crystalline ultrathin Au nanosheets with large areas over 100 μm 2 .…”
Section: Synthetic Methodsmentioning
confidence: 99%
“…For example, an iridescent hexadecylglyceryl maleate (HGM) hydrogel has been used to synthesize single-crystalline ultrathin Au nanosheets with large areas over 100 μm 2 . 41 It was found that the HGM hydrogel consisted of a periodically regular sandwich structure of lamellar bilayer membranes and 100 nm-thick water layers, which could function as a 2D template to guide the growth of ultrathin Au nanosheets from HAuCl 4 . Note that the surface of these large Au nanosheets is atomically smooth.…”
Section: Synthetic Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretically, FUMNSs with atomic thickness possess great advantages over their bulk counterparts, since they expose surface atoms to the largest extent, so as to exhibit unique physical and chemical properties. Hence, FUMNSs have attracted considerable devotion, which has brought some exciting breakthroughs recently . For instance, Zheng and co‐workers reported the synthesis of ultrathin hexagonal palladium (Pd) NSs with a uniform thickness of 1.8 nm ( Figure a), which show promising applications in photothermal therapy.…”
Section: Introductionmentioning
confidence: 99%